Physico-chemical studies of solutions of some acids in acetone - Sadie, Francois Gustaves du Bois (Department of Chemistry, 2016)
The work of Hotz showed the lack of knowledge of the behaviour of electrolytes in acetone solutions as well as the uncertainty as to the possibility of preparing anhydrous acetone and the stability of this solvent, if it could be prepared. An extensive study was therefore undertaken in which the efficiency of various desiccants was studied in producing acetone as anhydrous as could be obtained. A very efficient still was designed and the average water content of the acetone produced was of the order of 0.006 per cent which is much lower than reported by any previous investigator. Moisture determinations were done using a modified Karl Fischer reagent.